PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR SISWA - Diana Sari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The objective of this research to know how the role of parents in the students’ learning motivation. Type of research is qualitative research. Research was conducted in class VIII SMP Negeri 3 Palembang, with subject of 5 students and 5 parents of students. Methods for data collection is used interview, observation and document. Data analysis using descriptive qualitative analysis. Parents have important role to develop the of their children capability. Parents are first and have main educators in the family environment, it needed maximum effort to be educate children in all aspects of developed and increased the role of parents as educators in family. Therefore, parents have important role especially in determine education for children. Parents should be able to condition for family environment to support children's education. Parents' involvement in the education of their children motivated them quickly..  The results showed the role of parents in the students’ learning motivation. First subject, parent had high role in the students’ learning motivation, the subject had high in learning motivation. Second subject, parents had low role in the students’ learning motivation, the subject had low in learning motivation. Third subject, parents had average in the students’ learning motivation, subject had average in learning motivation. Fourth subject had high role in the students’ learning motivation, subject had high in learning motivation. Fifth subjects parents had low role in the students’ learning motivation, subject had low in learning motivation.